The Revival of St Menas Veneration in the Twentieth-Century Egypt - Miyokawa, Hiroko (Vox Patrum, 2025)
In antiquity, St Menas was highly revered throughout the Christian world and attracted large numbers of pilgrims to the pilgrimage centre of Abū Mīnā. In twentieth-century Egypt, however, this saint became a figure of limited recognition in the Coptic Orthodox community. The revival of St Menas’s veneration, promoted by the Patriarch of the Coptic Orthodox Church, Cyril VI, made the saint very popular in contemporary Coptic society. In this article, I argue that the resurgence of St Menas’s veneration stemmed not only from Cyril VI’s dissemination efforts rased on religious motivations, but also from Coptic cultural nationalist motivations, led by the Coptic laity. The miraculous story that emerged during the Second World War among the Greek soldiers, and the nationalist response of a dozen Coptic lay youth in Alexandria, played an important role in the campaign to reevaluate the Coptic past symbolised by St Menas and his pilgrim centre of Abū Mīnā.